Field evaluation of a semi-automatic vegetable transplanter for major vegetable crops - BHAMBOTA, S; DIXIT, A K; MANES, G S; DHATT, A S; SINGH, S K; SINGH, ARSHDEEP (The Indian Journal of Agricultural Sciences, 2018)
A tractor operated semi-automatic two row vegetable transplanter using plug type nursery was developed. This machine makes ridges with provisions to vary row and plant spacing. Machine released the seedlings close to the ground in near vertical position without any damage. Machine was evaluated in the field for transplanting tomato, brinjal, and chilli nursery at forward speeds of 1.00, 1.25, and 1.50 km/h. Plug type nursery was used which was grown in trays having truncated pyramid shape cells of volume 16.28 cm3 using soil-less media developed by Punjab Agricultural University. Plant missing, plant doubling, and quality of feed index was adversely affected at higher forward speeds for tomato and brinjal. Quality of feed index was 100 % for chilli up to highest forward speed of 1.5km/h. The machine can transplant tomato, brinjal and chilli at forward speed of 1.00 km/h, 1.25 km/h, and 1.50 km/h respectively with plant missing of less than 4% at these recommended speeds. The machine could transplant the seedlings with inclinations less than 30°, which is considered erect. No plant mortality was observed after 20 days for all the crops studied. Field capacity of the machine for transplanting tomato, brinjal and chilli was 0.103 ha/h, 0.126ha/h, and 0.152 ha/h, respectively as recommended for these cops. Saving in labour with the use of the machine over manual method for transplanting tomato, brinjal and chilli was 84.86%, 85.58%, and 88.41%, respectively, whereas saving in cost was 24.80%, 28.03% and 42.42%, respectively.